Focus on TILs: Prognostic significance of tumor infiltrating lymphocytes in head and neck cancers - Uppaluri, Ravindra (Academy of Cancer Immunology, 2008)
The expanding and established literature that correlates tumor infiltrating lymphocytes (TILs) with outcomes of patients with solid tumors has contributed greatly to the appreciation of the interaction between the host immune system with neoplastic growth. This analysis has been limited to specific tumors, such as melanoma and ovarian cancer, and our understanding of TILs in relation to many other malignancies has yet to be explored. We review one less well studied malignancy, head and neck squamous cell carcinoma (HNSCC), and the initial attempts to examine the impact of TILs on outcomes of these patients. To provide a context for the discussion of TILs and HNSCC, we first review the epidemiology, relevant head and neck anatomy, immune responses and discuss the historical data regarding the unique immunobiology of these tumors. Finally, with this perspective, we describe our current understanding of tumor infiltrating lymphocyte data for head and neck cancers.